An Economic Reform Agenda for Croatia: a comprehensive economic reform package prepared for the Croatian Statehood Foundation (Zaklada Hrvatskog Drzavnog Zavjeta) - Oliver Falck; Siegfried Schönherr (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2016)
Since the outbreak of the financial crisis Croatia has faced negative growth rates and Foreign Direct Investment has not recovered since. This has resulted in a steadily growing brain drain of highly qualified labor. The economy's international competitiveness has been decreasing for quite some time, and has now fallen to one of the last positions in the European ranking. Economic analysts and many politicians agree that the country's development is blocked by not being able to reform. Implementation of the necessary reforms is a precondition for any return to sustainable growth. This collected volume presents a comprehensive economic reform agenda for Croatia. The analyses focus on reform areas such as FDI and exports, exchange rates, labor markets, private debt, public finance, regulations of private enterprise, social security, human capital, technology and innovations, as well as infrastructure, especially energy. The reform concepts presented in each chapter of this volume were discussed in workshops with Croatian academics and stakeholders and condensed into a final comprehensive and feasible reform agenda. – – Seit der Finanzkrise hat Kroatien negative Wachstumsraten. Der Brain Drain hochqualifizierter Arbeitskräfte nimmt stetig zu. Die Wirtschaft hat schon seit längerer Zeit starke Einbußen ihrer Wettbewerbsfähigkeit erfahren. Kroatien rangiert diesbezüglich am Ende der Skala der EU-Mitglieder. Das Land befindet sich in einem Reformstau, der überwunden werden muss, damit Kroatien wieder auf einen nachhaltigen Wachstumskurs gelangt. Dieser Sammelband beschreibt eine wirtschaftspolitische Reformagenda für Kroatien. Schwerpunkt der Analysen bilden die Reformfelder Auslandsdirektinvestitionen und Exporte, Wechselkurse, Arbeitsmärkte, private Verschuldung, öffentliche Haushalte, Regulierungen für Unternehmen, Sozialsysteme und Alterssicherung, Humankapital, Technologie und Innovation sowie Infrastruktur mit dem Schwerpunkt Energie. Die zu den einzelnen Bereichen verfassten Analysen wurden in mehreren Workshops unter Beteiligung kroatischer Wissenschaftler und Stakeholder diskutiert und abschließend zu einem integrierten schlüssigen Reformkonzept zusammengefasst.
Keywords: O11; 330; Wirtschaftswachstum; Finanzkrise; Krise; Brain Drain; Wettbewerb; Wirtschaftspolitik; Wirtschaftsreform; Kroatien; Wirtschaftsreform; Wirtschaftspolitik; Arbeitsmarktreform; Rentenreform; Bildungspolitik; Haushaltskonsolidierung; Mittelstandspolitik; Infrastrukturpolitik; Technologiepolitik; Kroatien